The role of mastery in Crohn’s disease: a cross-sectional study - Marina Francesca Gattoni; Enrica Previtali; Salvatore Leone; Alessia Amore; Eleonora Volpato (Therapeutic Advances in Gastroenterology)
Background: Crohn’s disease (CD) is a chronic autoimmune inflammatory bowel disease. It is estimated that approximately 40% of individuals with CD are non-adherent to medical prescriptions. This lack of adherence to treatment plans has been linked to an increased risk of hospitalisation and surgical procedures, which can have a detrimental impact on the patient’s quality of life (QoL). Furthermore, the CD can impose significant stress on individuals, affecting their mental health and sense of mastery. The term ‘mastery’ is used to describe an individual’s awareness of their abilities and capacities that are essential for effectively managing life events and situations. Objectives: This study aimed to investigate the role of mastery in relation to medical adherence, distress, perceived social support, QoL, depressive and anxious symptoms and interoception in persons with a diagnosis of CD. Design: This is a cross-sectional study, involving 261 adults diagnosed with CD. Methods: Participants completed an online questionnaire comprising validated clinical and psychological scales, which lasted approximately 20 min. Participants were permitted to provide their most recently available medical report. Results: Patients with CD reported discrete levels of mastery. Two factorial ANOVA highlighted statistically significative differences in mastery in relation to clinical conditions ( F (2, 253) = 11.22, p  < 0.001) and a significative interaction effect between gender and symptomatology ( F (2, 253) = 7.22, p  < 0.001). Multiple linear regression illustrated a statistically significant association between mastery, clinical conditions, QoL, stress and interoception (adjusted R square = 0.558; F (14, 211) = 21.32, p  < 0.001). Concerning the possible mediator role of mastery between psychological state and medical adherence, no statistically significant results emerged from the mediation model analysis. Conclusion: This study highlighted an effective impairment of mastery in CD patients, especially among men experiencing mild disease activity. A positive association between mastery and enteroception was outlined. The higher prevalence of distress, anxiety and depressive symptoms connected to mastery was substantiated. Future research should deepen the relationship between mastery with medical adherence.